Organizational Mission Statements of the Best and Biggest Companies in Brazil - Lugoboni, Leonardo Fabris (2019)
The concern with outcomes and best practices is part of the daily life of managers and companies, including the concern with strategic planning. Within this context, this research aims to answer the following question: What is the organizational structure of the mission statements of the companies classified as "Biggest and Best" in Brazil? For this we analyze the organizational mission of the 500 best companies classified by ranking "Best and Biggest of 2012" by Abril publisher. It was observed that the main aspects are: "Identification of self-concept and core values, philosophy, technology and core competencies and organizational behavior"; "products and services" and "sustainable issues" (social and environmental). "Although it is not possible to say that the presence or absence of the aspects in their missions are responsible for the performance of companies, we can say that these aspects are present in the organizational mission of the 500 Best and Biggest of 2012.